Peran Kepemimpinan Kharismatik Dan Transformasional Dalam Mendorong Inovasi Di Pondok Pesantren Jauharul Falah - Zufadli Zufadli; Jamrizal Jamrizal; Kasful Anwar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to explore and understand the role of charismatic and transformational leadership in the context of thejauharul Falah Islamic Boarding School and how this role influences the innovation process at this institution. In an effort to face the challenges and rapid developments in the modern educational era, it is important to understand how leadership can be a driving force for innovation in traditional Islamic educational institutions.This research adopted a qualitative approach and carried out in-depth analysis through interviews and observations of leaders, teachers and administrative staff at the Islamic Boarding School of Pesantrenjauharul Falah. The research findings reveal that charismatic and transformational leadership plays a central role in shaping the culture of innovation at this institution. Charismatic leadership is able to motivate stakeholders, while transformational leadership inspires positive changes in education and institutional management. The results of field data analysis highlight charismatic and transformational leadership practices that support innovation. Leaders at the Islamic Boarding School Pesantrenjauharul Falah have the ability to create a shared vision and motivate individuals to actively participate in innovation efforts. Furthermore, this research illustrates how innovative changes in curriculum, teaching methods, and institutional management have supported the growth of this Islamic boarding school.Thus, this research provides an important contribution to the understanding of the relationship between charismatic and transformational leadership and innovation in Islamic educational institutions. The implications of this research can provide guidance for similar educational institutions to optimize the role of their leaders in encouraging innovation that is relevant to the demands of the times.